Marcel Dupré's “Dark Years”: Unveiling His Occupation-Period Concertizing - Cavanagh, Lynn (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2014)
Examination of organist Marcel Dupré’s collected concert programs reveals that, of 137 he performed during the German occupation, 14 bear signs of funding by the German Embassy or the military government’s Propaganda Department. Dupré, though, would have participated in good conscience out of personal pride in France’s musical past. Post-Liberation punishments of French musicians who “collaborated with the enemy” were applied so inconsistently as to explain why he thereafter suppressed the extent and nature of his Occupation-period concertizing. This fuller picture of his activities potentially sheds light on his Second World War–period compositions, particularly Évocation, op. 37.